Decreased spacing with different numbers of branches to enhance green fig production - Pio, Rafael; Sanchez, Oscar Misael Peralta; Ribeiro, Carlos Henrique Milagres; Fazenda, Lucídio Henriques Vote; Silva, Alexandre Dias da; Peche, Pedro Maranha (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the effect of decreased spacing between 'Roxo de Valinhos' fig (Ficus carica) trees with different numbers of fruiting branches on green fig production. Fig trees, with two or four fruiting branches, were distributed in four blocks, at a standard spacing of 2.5 m between rows, three spacing between plants in a row (0.50, 0.75, and 1.00 m), and densities of 8,000, 5,333, and 4,000 plants per hectare. The experiment was conducted during two cycles (2020/2021 and 2021/2022). Green fruits were harvested twice a week, and the total number of fruits per harvest and the total harvest weight per plant were quantified. The average production per plant and the estimated yield were calculated for each evaluation cycle. Decreasing the spacing between fig trees increases their yield. The spacing of 0.50 m decreases production per plant, but increases yield in 73%. There is no difference in the production of green figs between trees with two or four fruiting branches.